علاقة استراتيجية مواجهة الضغوط النفسية بالمرونة النفسية - بن مصباح,هاجر; علوان,ليلى (University of Eloued جامعة الوادي, 2024)
The study aimed to identify the strategy of coping with psychological stress and its relationship to psychological resilience among university students, The descriptive correlational approach was adopted, and the study included a sample of (200) male and female students in the Department of Psychology and Educational Sciences at the University of Martyr Hama Lakhdar in El Oued, where they were selected in a stratified random manner, and the psychological stress coping strategy scale and the psychological resilience scale were applied, and to process and analyze the data statistically, the SPSS statistical program was used based on the Pearson correlation coefficient, which showed us the following results: - There is a statistically significant correlation between the strategy of coping with psychological stress and psychological resilience among university students. - There is a statistically significant positive correlation between the strategy of coping with psychological stress and emotional resilience among university students. - There is a statistically significant positive correlation between the strategy of coping with psychological stress and mental resilience among university students. - There is a statistically significant positive correlation between the strategy of coping with psychological stress and social resilience among university students. هدفت الدراسة إلى التعرف على إستراتيجية مواجهة الضغوط النفسية وعلاقتها بالمرونة النفسية لدى طلبة الجامعة، حيث تم اعتماد المنهج الوصفي الارتباطي، وشملت الدراسة على عينة قوامها (200) طالب وطالبة بقسم علم النفس وعلوم التربية بجامعة الشهيد حمه لخضر بالوادي، حيث تم إختيارهم بطريقة عشوائية طبقية، وتم تطبيق مقياس استراتيجية المواجهة الضغوط النفسية ومقياس المرونة النفسية، ولمعالجة البيانات وتحليلها إحصائيا تم إستخدام البرنامج الاحصائي SPSS بالاعتماد على معامل الارتباط بيرسون، حيث أظهر لنا النتائج التالية: - توجد علاقة إرتباطية ذات دلالة إحصائية بين استراتيجية المواجهة الضغوط النفسية والمرونة النفسية لدى طلبة الجامعة. - توجد علاقة ارتباطية ذات دلالة إحصائية موجبة بين استراتيجية مواجهة الضغوط النفسية والمرونة الانفعالية لدى طلبة الجامعة. - توجد علاقة ارتباطية ذات دلالة إحصائية موجبة بين استراتيجية مواجهة الضغوط النفسية والمرونة العقلية لدى طلبة الجامعة. - توجد علاقة ارتباطية ذات دلالة إحصائية موجبة بين استراتيجية مواجهة الضغوط النفسية والمرونة الاجتماعية لدى طلبة الجامعة.
Keywords: إستراتيجية المواجهة; الضغوط النفسية; المرونة النفسية; Coping strategy; psychological stress; psychological resilience